Reducing single-use plastics (SUPs) consumption: A synthesis of I and S level approaches - Pham Van Hau; Kirsten Robertson; Maree Thyne; Robert Hamlin; Sharyn Rundle-Thiele (Sustainable Futures, 2025)
Single-use plastics (SUPs) pose significant global environmental challenges, emphasising the need for more effective intervention strategies. Existing reduction efforts often prioritise policy, legislative actions, or psychological interventions, but lack comprehensive guidance for future applications. This review categorises behaviour change interventions for SUPs reduction into individual-level (I-level) and system-level (S-level) approaches with three objectives: (1) synthesising current interventions into I-level and S-level categories, (2) examining their application across contexts, and (3) evaluating their impact on behavioural determinants. Quality was rigorously assessed using the ‘Quality Appraisal for Diverse Studies’ (QuADS) tool. From an initial search of over 900 peer-reviewed articles and additional searches, 41 studies met the criteria for inclusion. The findings indicated that I-level interventions, mostly educational campaigns, yield mixed outcomes with limited evidence of sustained behaviour change. Conversely, S-level interventions, mostly bans and market-based mechanisms (e.g., fees and levies), demonstrated higher efficacy, particularly when strongly enforced. Notably, none of the reviewed studies combined I-level and S-level approaches. Analysis using the Capability-Opportunity-Motivation-Behaviour (COM-B) model revealed that I-level interventions often enhanced ‘capability’ but overlooked ‘opportunity’, while S-level interventions created ‘opportunity’ but generally neglected ‘capability’. Both types of interventions are insufficiently targeted at ‘motivation’. This review underscores the urgent need for multi-faceted approaches that integrate both I-level and S-level strategies and engage stakeholders to bolster intervention effectiveness.